Novel X-linked genes revealed by quantitative polymerase chain reaction in the green anole, Anolis carolinensis - Rovatsos, Michail; Altmanová, Marie; Pokorná, Martina Johnson; Kratochvíl, Lukáš (G3 (Bethesda, Md.), 2014)
The green anole, Anolis carolinensis (ACA), is the model reptile for a vast array of biological disciplines. It was the first nonavian reptile to have its genome fully sequenced. During the genome project, the XX/XY system of sex chromosomes homologous to chicken chromosome 15 (GGA15) was revealed, and 106 X-linked genes were identified. We selected 38 genes located on eight scaffolds in ACA and having orthologs located on GGA15, then tested their linkage to ACA X chromosome by using comparative quantitative fluorescent real-time polymerase chain reaction applied to male and female genomic DNA. All tested genes appeared to be X-specific and not present on the Y chromosome. Assuming that all genes located on these scaffolds should be localized to the ACA X chromosome, we more than doubled the number of known X-linked genes in ACA, from 106 to 250. While demonstrating that the gene content of chromosome X in ACA and GGA15 is largely conserved, we nevertheless showed that numerous interchromosomal rearrangements had occurred since the splitting of the chicken and anole evolutionary lineages. The presence of many ACA X-specific genes localized to distinct contigs indicates that the ACA Y chromosome should be highly degenerated, having lost a large amount of its original gene content during evolution. The identification of novel genes linked to the X chromosome and absent on the Y chromosome in the model lizard species contributes to ongoing research as to the evolution of sex determination in reptiles and provides important information for future comparative and functional genomics.
Keywords: Gene Dosage; sex chromosomes; sexuální faktory; genetics of sex; lizard; sex determination; Sex Factors; Genes, X-Linked; Female; genová dávka; gene dosage; genetická vazba; geny vázané na chromozom X; Lizards; mužské pohlaví; zvířata; ženské pohlaví; ještěři; Conserved Sequence; Genetic Linkage; Animals; Male; qPCR; konzervovaná sekvence